2016
DOI: 10.1016/j.atmosenv.2016.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal surface ozone enhancement over Portugal during winter: Influence of different atmospheric conditions

Abstract: h i g h l i g h t s4 distinct events of nocturnal surface ozone (NSO) enhancement were analyzed. WRF model was used to simulate the atmospheric conditions during NSO enhancement. Results show that different atmospheric mechanisms are responsible for each event.a r t i c l e i n f o a b s t r a c tFour distinct nocturnal surface ozone (NSO) enhancement events were observed, with NSO concentration exceeding 80mg/m 3 , at multiple ozone (O 3 ) monitoring stations (32 sites) in January, November and December betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 42 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Thus, this case presents how the development of boundary layer low-level jets triggers NOE events. The lowlevel jets have also been identified as a key factor causing multiple NOE events in different regions in China Wu et al, 2022), the US (Kuang et al, 2011;Hu et al, 2013;Sullivan et al, 2017;Caputi et al, 2019), and Europe (Kulkarni et al, 2016;Klein et al, 2019). tion, lifting the surface ozone level from 9 to 34 ppbv.…”
Section: Case Studies Of Noe Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this case presents how the development of boundary layer low-level jets triggers NOE events. The lowlevel jets have also been identified as a key factor causing multiple NOE events in different regions in China Wu et al, 2022), the US (Kuang et al, 2011;Hu et al, 2013;Sullivan et al, 2017;Caputi et al, 2019), and Europe (Kulkarni et al, 2016;Klein et al, 2019). tion, lifting the surface ozone level from 9 to 34 ppbv.…”
Section: Case Studies Of Noe Eventsmentioning
confidence: 99%
“…A number of studies have reported episodic nocturnal ozone enhancement events at individual sites around the world (Eliasson et al, 2003;Hu et al, 2012Hu et al, , 2013Klein et al, 2014;Kulkarni et al, 2016;Caputi et al, 2019;He et al, 2021). The reported nocturnal ozone enhancements mostly ranged from 5 to 30 ppbv, but they were found to be up to 70 ppbv in an extreme event observed in summer 2013 over the North China Plain (Jia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In their review article, Wei et al (2023) suggest that LLJs are a common feature and they discuss the implications this may have on the dispersion of gases and particulates. Wei et al (2023) indicate that LLJs have at least two effects on air concentrations: (a) decreases due to long‐range advection of pollutants above the LLJ (Banta et al, 1998; Corsmeier et al, 1997; Klein et al, 2019; Martins et al, 2018) and (b) increases below the LLJ due to downward momentum brought about by the enhanced vertical wind shear (Fiedler et al, 2013; Karipot et al, 2006; Kulkarni et al, 2016; Schepanski et al, 2009). Our results are consistent with the first of these effects.…”
Section: Resultsmentioning
confidence: 99%
“…This event results from the horizontal and vertical transport of ozone and its precursors [13]. Studies of nocturnal ozone concentration increase were developed in the Portuguese continent to explain unexpected ozone levels [21,36]. The ozone enhancement events can be related to transport processes and the related usual meteorological conditions due to the absence of photochemical production.…”
Section: Surface Ozone At Rural Stationsmentioning
confidence: 99%